Atores, cenários e planos: o planejamento estratégico situacional e a educação - Gentilini, João Augusto [UNESP] (Fundação Carlos Chagas, 2014)
This study addresses the current planning model in Latin America, which was inspired by the thought of national development granting the State the role of the leading actor of economic development. It examines the influence of this model on the planning of social arenas, including the educational one and inquires the factors that led to its breakdown. The criticisms of the fundamental postulates of traditional economic planning in the late 1970s and the post-80s crisis, and the search for alternative proposals of planning are also adressed. Finally, the study deals with Carlos Matus´s Situational Strategic Planning (PES method), covering the main operational concepts of the method of this intellectual and economist altogether its suitability for the program of the social and educational areas.

Este texto aborda o modelo de planejamento vigente na América Latina, inspirado no pensamento nacional-desenvolvimentista, tendo o Estado como ator principal do desenvolvimento econômico. Examina a influência desse modelo sobre o planejamento das áreas sociais, inclusive da área educacional e os fatores que levaram ao seu esgotamento. As críticas surgidas aos postulados fundamentais do planejamento tradicional de natureza econômica no final da década de 1970 e pós-crise dos anos de 1980 e a busca de propostas alternativas de planejamento também são explicitadas, assim como a proposição do Planejamento Estratégico Situacional (Método PES), do intelectual e economista Carlos Matus, abrangendo seus principais conceitos operacionais e sua adequabilidade ao programa da área social e educacional.

Será aquí abordado el modelo de planificación vigente en América Latina, inspirado en el pensamiento nacional-desarrollista, teniendo el Estado como actor principal del desarrollo económico; la influencia de ese modelo sobre la planificación de las áreas sociales, inclusive del área educativa y los factores que llevaron a su agotamiento; las críticas surgidas a los postulados fundamentales de la planificación tradicional de naturaleza económica al final de la década de 1970 y post-crisis de los años de 1980 y la búsqueda de propuestas alternativas de planificación; así como la proposición de la Planificación Estratégica Situacional (Método PES), del intelectual y economista Carlos Matus, incluyendo sus principales conceptos operacionales y su adaptabilidad al programa del área social y educativa.
Actores, escenarios y planos: la planificación estratégica situacional y la educación
Actors, scenarios and plans: situational strategic planning and education
Keywords: Planejamento estratégico situacional; governabilidade; planejamento da educação; Situational strategic planning; governance; educational planning